Nationalism, Secularism and Liberal Neutrality: The Danish Case of Judges and Religious Symbols - Holtug, Nils (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2011)
In 2009, a law was passed in the Danish parliament, according to which judges cannot wear religious symbols in courts of law. First, I trace the development of this legislation from resistance to Muslim religious practices on the nationalist right to ideas in mainstream Danish politics about secularism and state neutrality – a process I refer to as ‘liberalization’. Second, I consider the plausibility of such liberal justifications for restrictions on religious symbols in the public sphere and, in particular, for the ban on the wearing of religious symbols by judges. I argue that such justifications are flawed and so are not plausible corollaries of anti-Islamic justifications originating on the nationalist right.